Endoscopic Management of Perforation of Right Hepatic Duct Following Non-Surgical Abdominal Trauma. Issue 4 (1997) - Sharma, B. C.; Maini, A.; Saraswat, V. A.
Abstract : Isolated bile duct injuries after blunt abdominal trauma are rare. Surgery is the usual mode of treatment. We report a patient with a right hepatic duct injury following blunt abdominal trauma who was managed successfully by endoscopic papillotomy.